COCONUT OIL EFFECT IN THE COMPLICATIONS OF HEPACTIC DISEASE - Piedade, Giovanna Santos (2022)
Background: Prevention of the progression of cirrhosis with dietary supplementation has been in focus Coconut oil has been suggested. Objective: To evaluate the effect of coconut oil supplementation in cirrhotic rats. Method: Forty Wistars were divided: control (CO), control + coconut oil (CO + OC), thioacetamide (TAA) and thioacetamide + coconut oil (TAA + OC). TAA was added to water for 13 weeks and coconut oil was administered by gavage. Blood, liver, muscle and nervous tissue samples were obtained for laboratory and histopathological analyses. Results: AST, ALT, total cholesterol, HDL, LDL, triglycerides were not statistically significant. In histology, even without differences, there was a tendency towards significance regarding the proliferation of bile ducts, fibrotic septa and muscle fiber atrophy between the TAA and TAA + OC groups. Conclusion: No significant protective effect of coconut oil on liver disease was found.